Penggunaan Teknologi Informasi dalam Pembelajaran Online Masa Covid-19 - Aufia Aisa; Linta Lisvita (JoEMS (Journal of Education and Management Studies), 2020)
The Covid-19 pandemic affects almost all aspects of life, including education. The impact of the Covid-19 pandemic on the education aspect requires that teaching and learning activities continue even though students are at home. So that educators are required to design learning media as an innovation by utilizing online media. The purpose of writing this article is to study and understand the use of information technology in online learning during the Covid-19 period. The writing of this article uses a qualitative approach with secondary data sources obtained from online observations and literature studies. The results of the study prove that the use of online media during the Covid-19 caused a variety of responses and the impact and change in the learning system that can affect the teaching and learning process as well as the level of student development in responding to the material presented.